Lexical and grammatical access errors in the speech of intermediate/advanced level students of spanish - Lafford, Bárbara A.; Collentine, Joseph G. (Lenguas Modernas, 2017)
This paper is the first known analysis to investigate the lexical and grammatical access errors made by intermediate/advanced level students of Spanish as a foreign language in an American university setting. The data show that most of the errors committed at this level are paradigmatic in nature, i.e., neologisms, confusion of derivationally related forms, ser/estar, prepositions and conjunctions, and incorrect choice of gender, mood, tense and person. The most common syntagmatic errors are those involving omission or addition of function words and anaphoric agreement of gender, number and person. In general, these findings concur with other studies of the acquisition of Spanish as a second language by Anglo adults.